Ser velho: a construção da velhice em três filmes brasileiros - Yamanaka, Juliane Domingos [UNIFESP] (2016)
This research means to understand the possible constructions of old age in three Brazilian movies and which would be the role of social relationships and sociability in these constructions. My aim falls over the films: Depois daquele baile, (Roberto Bomtempo, 2005), O outro lado da rua (Marcos Bernstein, 2004) e Onde anda você (Sergio Rezende, 2004). We understand that movies carry a symbolic load elucidated through narratives, soundtracks, planes, scenes among other elements, bringing the possibility of discussing the living in old age nowadays from perspectives that not always match, what brings a problematization to the subject. Specially, I emphasize old age amidst an urban experience, considering this to be a privileged contest in the movies I'm analyzing. The old age, in this paper, is treated in the complexity the subject demands: multiple, field of public policies and social representations. The Cinema, on the other hand, configures a privileged place for this discussion, precisely due the way it allows this complexity to be symbolically treated.